A comparative study on the rheological, thermal, and mechanical performance of epoxy resin modified with thermoplastics. Issue 13 (3rd July 2021) - Li, Hongfeng; Zhao, Liwei; Su, Kai; Feng, Hao; Wang, Dezhi; Qu, Chunyan
Abstract: Thermoplastics and functional polymers are commonly used modifiers for epoxy (EP) resin. In this study, an EP system was fabricated and modified with methyl methacrylate block copolymer (BMG), polyphenylene oxide (PPO) and polysulfone (PSF). This was carried out to study the influence of thermoplastic polymers and functional polymers on the properties of EP resins, and the performance of the different modified EP systems was studied and compared. The curing reaction, rheological performances, heat resistance, and mechanical properties of the EP blends were investigated. Curing process of EP resin was determined as 110 °C for 1 h and 150 °C for 3 h by using non-isothermal differential scanning calorimetry (DSC) method. The rheological test revealed that the EP/BMG and EP/PPO blends exhibited low viscosity and wide processing window compared to the EP/PSF blend, thereby indicating good processing performance. The thermal stability of the modified EP blends was evaluated by using dynamic mechanical analysis methods. The results showed that the glass transition temperature ( Tg ) of EP/BMG, EP/PPO and EP/PSF blends were 123 °C, 129 °C, and 131 °C, respectively. BMG showed an excellent toughening effect on EP resin compared to PPO and PSF. In addition, the flexural strength and impact strength of EP/BMG were 114 MPa and 21.2 kJ/m 2, respectively. The influence of polymers on the properties of EP resin stems from their molecular structures.